Outbreak of acute diarrhea in children: Clinical manifestations, treatment, source of drinking water, and fecal microbiome analysis in region of West Sumatra Province, Indonesia - Dianne Jurnalis Yusri; Yugatama Andyan; Azka Neila; Fenobileri Nice (E3S Web of Conferences)
In April 2024, a severe diarrhea outbreak in Pesisir Selatan Regency, triggered by floods, led to 355 reported cases and five pediatric deaths. A rapid response team conducted a comprehensive investigation in two phases of research as countermeasure. Phase one involved data collection from medical records. Correlation between variables, nutritional status and difference of treatment between two health facilities, with length of stay (LoS). Phase two are PCR examination of fecal samples and examination of total coliform and Escherichia coli bacteria from drinking waters. Subjects predominantly aged 0–5 years (86.5%). Probiotic and intravenous 28.4 antibiotic were significantly correlated with shorter LoS (p<0.05). There are 4% malnutrition subjects with the longest LoS. Drinking water from the house of deceased patients was contaminated, with the highest total coliform of 6800 CFU/100 mL and from public water depots at 7800 CFU/100 mL. Fecal samples identified Escherichia coli as the primary pathogen responsible for the outbreak. The findings emphasize the importance of nutrition status, prompt medical treatment including probiotics and proper antibiotics as an effective treatment protocol and highlight urgent need to enhance water quality and sanitation to prevent diarrhea outbreaks in the future.